2017
DOI: 10.21037/tau.2017.09.17
|View full text |Cite
|
Sign up to set email alerts
|

Real world treatment patterns in the neurogenic bladder population: a systematic literature review

Abstract: Myriad treatment modalities are available for neurogenic bladder (NGB) including behavioral therapies, oral pharmacotherapy, catheterization and surgical procedures. Little is known about how NGB patients are managed in the real world, how well patterns relate to clinical guidelines and how strategies may have changed over time. To address this gap, a systematic review (SR) was conducted using MEDLINE and EMBASE [1996–2017]. The inclusion criteria for studies were: (I) published in English; (II) conducted in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although IC is considered the standard bladder evacuation method in NLUTD, little is known about how this recommendation is implemented in community-based life. To the best of our knowledge, there has been no published data regarding the required amount and type of urological A recent systematic review 5 on treatment patterns in neurogenic bladder patients reported a percentage of patients with IC varying between 0% and 84% with very low rates in two older studies in the US (30.5%, 29.1% 9,10 ). In more recent studies in Switzerland, the Netherlands, the US and Turkey 6,[11][12][13] the percentage was 41.3%, 42.6%, 59.2% and 77.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IC is considered the standard bladder evacuation method in NLUTD, little is known about how this recommendation is implemented in community-based life. To the best of our knowledge, there has been no published data regarding the required amount and type of urological A recent systematic review 5 on treatment patterns in neurogenic bladder patients reported a percentage of patients with IC varying between 0% and 84% with very low rates in two older studies in the US (30.5%, 29.1% 9,10 ). In more recent studies in Switzerland, the Netherlands, the US and Turkey 6,[11][12][13] the percentage was 41.3%, 42.6%, 59.2% and 77.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…One essential prerequisite for a long-term outcome with a low complication rate is the provision of an adequate quantity of high-quality urological aids and appliances. 3,4 To date, there have been few dedicated investigations on the actual individual voiding mode 5,6 and the number of bladder evacuations per day in outpatients with NLUTD. This results in a lack of objective data on the quantity of the urological aids and appliances needed.…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenic lower urinary tract dysfunction (NLUTD) is defined as lower urinary tract symptoms secondary to neurological disease or central nervous system (CNS) injury [1][2][3][4] that results in disturbance of ascending or descending pathways to the bladder 5 . The International Continence Society (ICS) classify NLUTD based on clinical symptoms including storage phase symptoms, voiding phase symptoms, and post-micturition symptoms 1 .…”
Section: Introductionmentioning
confidence: 99%